The Influence of Social Media on Mazmumah Morals in Students of SMP Negeri 34 Samarinda - Siswanto, Adi; Armella, Rega; Hidayat, Ahmad Fadhel Syakir (Borneo Journal of Islamic Education, 2023)
This research is motivated by the fact that easy and equitable access to the Internet has now permeated various levels of society, including among students at SMP Negeri 34 Samarinda. Social media, as a manifestation of this development, has a significant impact on the moral dimension of individuals. Observations at this school indicate that students are quite active in accessing social media, with examples of platforms often used, such as WhatsApp, Instagram, and TikTok. Therefore, this study aims to determine the extent of the influence of social media on the mazmumah morals of students at SMP Negeri 34 Samarinda. The research method used is quantitative with an ex post facto approach. Sample determination was done through purposive sampling, and data collection used a Likert scale. Data analysis involved correlation coefficient hypothesis testing and simple linear regression testing. The findings showed that out of a total of 195 grade VIII students, 190 had social media accounts (Instagram, WhatsApp, and TikTok), and 70 actively accessed social media. The analysis results confirmed the influence between social media and mazmumah morals of students at SMP Negeri 34 Samarinda. Hypothesis testing resulted in a significance value of 0.000 <0.05, indicating acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (H0). The correlation test shows a Pearson correlation value of -0.440, indicating a moderate relationship with a negative direction between the social media variable (X) and mazmumah morals (Y). Keywords: Influence, Social Media, Mazmumah Morals